Multiobjective Optimization Design and Performance Prediction of Centrifugal Pump Based on Orthogonal Test - Yuqin Wang; Xinwang Huo (Advances in Materials Science and Engineering)
In order to improve the hydraulic performance of the centrifugal pump, based on the original model, the optimization mathematical model with the four indexes head, efficiency, shaft power, and pump net positive suction head as objective function was established, and the multiobjective optimization design of the centrifugal pump was carried out by orthogonal test. Based on the L1644 orthogonal table, 16 sets of orthogonal test schemes were made by selecting the four parameters impeller outlet width, blade inlet angle, blade outlet angle, and cape angle; the flow field numerical simulation was carried out by computational fluid dynamics technique; and the influence order of geometric parameters on optimization indexes was obtained by range analysis. The weight of each test factor on the optimization index was calculated by weight matrix, and a set of optimal schemes was obtained. Based on the external characteristic experimental bench of the IH 65-60-190 chemical centrifugal pump, the simulation values and test values of the prototype pump and the optimization pump were obtained under different working conditions. Under the rated flow, the head was reduced by 17.00%, the efficiency was increased by 9.14%, the shaft power was reduced by 21.50%, the pump net positive suction head was reduced by 16.69%, the curve hump was eliminated, the performance of centrifugal pump was improved, and the feasibility of the weight matrix optimization method was verified. The particle image velocimetry measurement system was used to measure the relative velocity of the internal media in the centrifugal pump. The results showed that the optimization pump had no obvious “jet-wake” flow structure, its maximum velocity was less than the prototype pump, the area of low-speed zone was larger than the prototype pump, the efficiency of the centrifugal pump was improved, and the shaft power and pump net positive suction head were reduced. The reason of the head decrease was analyzed from the internal flow situation, and the accuracy of the design optimization process was proved.